The changing sociocultural context of wildlife conservation. Issue 6 (27th June 2020) - Manfredo, Michael J.; Teel, Tara L.; Don Carlos, Andrew W.; Sullivan, Leeann; Bright, Alan D.; Dietsch, Alia M.; Bruskotter, Jeremy; Fulton, David
Abstract: We introduced a multilevel model of value shift to describe the changing social context of wildlife conservation. Our model depicts how cultural‐level processes driven by modernization (e.g., increased wealth, education, and urbanization) affect changes in individual‐level cognition that prompt a shift from domination to mutualism wildlife values. Domination values promote beliefs that wildlife should be used primarily to benefit humans, whereas mutualism values adopt a view that wildlife are part of one's social network and worthy of care and compassion. Such shifts create emergent effects (e.g., new interest groups) and challenges to wildlife management organizations (e.g., increased conflict) and dramatically alter the sociopolitical context of conservation decisions. Although this model is likely applicable to many modernized countries, we tested it with data from a 2017–2018 nationwide survey (mail and email panel) of 43, 949 residents in the United States. We conducted hierarchical linear modeling and correlational analysis to examine relationships. Modernization variables had strong state‐level effects on domination and mutualism. Higher levels of education, income, and urbanization were associated with higher percentages of mutualists and lower percentages of traditionalists, who have strong domination values. Values affected attitudes toward wildlife management challenges; for example, states with higher proportions of mutualists were less supportive of lethal control of wolves ( Canis lupus ) and had lower percentages of active hunters, who represent the traditional clientele of state wildlife agencies in the United States. We contend that agencies will need to embrace new strategies to engage and represent a growing segment of the public with mutualism values. Our model merits testing for application in other countries. Abstract : Article impact statement : Application of a multilevel model of social change reveals implications of a shift in public values for wildlife conservation in the United States. Abstract : El Cambiante Contexto Sociocultural de la Conservación de Fauna Resumen: Introdujimos un modelo multinivel del cambio de valores para describir el cambiante contexto social de la conservación de fauna. Nuestro modelo representa cómo los procesos a nivel cultural llevados por la modernización (p. ej.: aumento de riqueza, educación y urbanización) afectan a los cambios en la cognición a nivel individual que incitan a un cambio de los valores de dominación a los valores de mutualismo de la fauna. Los valores de dominación promueven la creencia de que la fauna debería usarse principalmente para beneficio de los humanos, mientras que los valores de mutualismo adoptan una visión de que la fauna es parte de la red social de uno y digna de cuidados y compasión. Dichos cambios generan efectos emergentes (p. ej.: nuevos grupos de interés) y retos para las organizaciones de manejo de fauna (p. ej.: conflictos mayores) y alteran dramáticamente el contexto sociopolítico de las decisiones de conservación. Aunque este modelo probablemente pueda aplicarse a muchos países modernizados, lo pusimos a prueba con datos de un censo nacional de 2017 ‐ 2018 realizado (por correo y correo electrónico) a 43, 949 residentes de los Estados Unidos. Realizamos un modelado jerárquico lineal y un análisis de correlación para examinar las relaciones. Las variables de modernización tuvieron efectos sólidos a nivel estatal sobre la dominación y el mutualismo. Los niveles altos de educación, ingresos y urbanización estuvieron asociados con los porcentajes más altos de mutualistas y con los porcentajes más bajos de tradicionalistas, quienes tienen valores de dominación fuertes. Los valores afectaron a las actitudes hacia los retos para el manejo de fauna; por ejemplo, los estados con proporciones mayores de mutualistas mostraron un menor apoyo para el control letal de los lobos ( Canis lupus ) y tuvieron porcentajes más bajos de cazadores activos, quienes representan a la clientela tradicional de las agencias estatales de vida silvestre en los Estados Unidos. Sostenemos que las agencias necesitarán adoptar nuevas estrategias para envolver y representar a un segmento creciente del público con valores mutualistas. Nuestro modelo amerita ser evaluado para su aplicación en otros países. 摘要: 本研究介绍了一个多层次的价值转移模型来描述野生动物保护中不断变化的社会背景。我们的模型描述了由现代化驱动的文化层面过程 (如财富、教育及城市化水平的提升) 如何影响个体层面的认知变化, 促使人们对野生动物的价值观从支配转向互惠。支配价值观倡导野生动物应主要用于造福人类, 而互惠价值观则认为野生动物是人类社会网络的一部分, 值得人们关爱和同情。这种价值观转变正在产生新的影响 (如新出现的利益团体), 并为野生动物管理组织带来了挑战 (如不断加剧的冲突), 同时极大地改变了保护决策的社会政治背景。上述模式可能适用于许多现代化国家, 本研究使用 2017‐2018 年对 43, 949 名美国居民进行全国性调查 (通过邮件和电子邮件面板) 的数据对其进行了测试。我们进行了多层线性建模和相关分析以检验变量间的关系。结果发现, 现代化变量在国家层面上对支配及互惠价值观有很强的影响。教育水平、收入水平和城市化水平越高, 互惠主义者的比例就越高, 同时具有强烈的支配价值观的传统主义者的比例越低。价值观影响着人们对野生动物管理挑战的态度;例如, 互惠主义者比例较高的州不太支持对狼 ( Canis lupus ) 进行捕杀控制, 积极捕猎者的比例也较低, 而这些人是美国国家野生动物机构的传统客户。我们认为, 各机构应采用新的策略来纳入及代表越来越多的持有互惠价值观的公众。我们的模型还可以在其他国家进行应用测试。【翻译: 胡怡思; 审校: 聂永刚】